Lateral Decubitus 360° Capsular Release for Treatment of Recalcitrant End-Stage Adhesive Capsulitis - Juan Bernardo Villarreal-Espinosa MD; Rodrigo Saad Berreta BA; Richard Danilkowicz MD; Udit Dave BS; Melissa Carpenter BS; Jorge Chahla MD, PhD; Nikhil N. Verma MD (Video Journal of Sports Medicine)
Background: Recalcitrant adhesive capsulitis, manifesting as persistent pain and continued range of motion deficits after a trial of conservative care, can be managed via lysis of adhesions with associated capsular release. While traditionally performed in the beach-chair position, capsular release performed via a lateral decubitus approach may provide enhanced visualization and the ability to perform a 360° release without iatrogenic injury to the cartilage surfaces. Indications: Arthroscopic capsular release in the setting of adhesive capsulitis is utilized when conservative strategies, such as physical therapy and/or corticosteroid injections, do not provide pain and range of motion improvement. Technique Description: Upon induction of general anesthesia, the patient is placed on the operating table in a lateral decubitus position utilizing the arm positioner of choice. The shoulder’s bony landmarks are identified for proper placement of the arthroscopic portals. A standard posterior portal is first established followed by an anterior portal in the rotator interval. Two-portal diagnostic arthroscopy then ensues. The rotator interval is then released, as is the superior capsule, to the 12-o’clock position using electrocautery. Next, a basket scissor is utilized to release the anterior capsule to the 6-o’clock position followed by posterior-superior and posterior-inferior capsular release while viewing anteriorly. Scope instrumentation is withdrawn and the shoulder manipulated, achieving full range of motion. Results: It is the senior author’s belief that by performing a capsular release via the lateral decubitus approach, better visualization, and access to the anterior, inferior, and posterior glenoid can be achieved for a complete 360° release. Additionally, risk of cerebral hypoperfusion and iatrogenic injury to the cartilage surfaces while instrumenting the joint is diminished. Upon procedure completion, the patient was observed to have gained full forward flexion, external rotation, and internal rotation. Discussion/Conclusion: Although traditionally approached via a beach-chair approach, capsular release of end-stage adhesive capsulitis via a lateral decubitus approach has shown to facilitate a circumferential view while providing ease of access to the inferior, anterior, and posterior glenoid, thereby substantially and immediately increasing patient range of motion. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.